How do Drama conventions maximise higher-order thinking in my Year 9 Drama scheme of work: The Hillsborough Disaster? - Webster, Charlotte (2013)
This dissertation undertakes a critical examination of how Drama can aid and develop higher-order thinking amongst students. This action research project is important to the development of my teaching practice and to Drama as a curriculum subject, in a time where Performing Arts and qualified Drama teachers are at risk. In recent years, government policy has placed increasing emphasis on students undertaking a more ‘rigorous’ curriculum. This government initiative stresses the importance of teaching core knowledge of facts and information, thus tending to promote ‘academic’ subjects only. However, the research included in this dissertation highlights how specific Drama conventions can support higher-order thinking, encouraging students to go beyond basic recall. The dissertation thus emphasises the importance of Drama and specialised Drama teachers as part of a broad, balanced and differentiated curriculum for students. The action research adopted in this dissertation investigates how my delivery of Drama conventions have helped develop higher-order thinking within a Year 9 class studying The Hillsborough Disaster. The findings from this research provide evidence that Drama conventions, delivered by a specialist Drama teacher, do develop complex thinking skills which are invaluable to developing higher-order thinking. Whilst carrying out the action research project, I have also developed a new Drama convention, moving mind, which supports non-verbal higher-order thinking. The dissertation also considers the possibilities and challenges of extending these findings to develop more general principles for teaching and learning in Drama.